Potential Dependent Mn Oxidation and Its Role in Passivation of Ni38Fe20Cr22Mn10Co10 Multi-Principal Element Alloy Using Multi-Element Resolved Atomic Emission Spectroelectrochemistry. Issue 5 (27th May 2021) - Han, Junsoo; Li, Xuejie; Gerard, Angela Y.; Lu, Pin; Saal, James E.; Frankel, Gerald S.; Ogle, Kevin; Scully, John R.
Abstract : The identity of passivating oxides on multi-principal element alloys is of great interest as their optimization offers the potential for exceptional corrosion resistance in aqueous solutions over a broad range of potential and pH. This study focuses on a non-equiatomic Ni38 Fe20 Cr22 Mn10 Co10 solid solution alloy and tracks the fate of each alloying element during linear sweep voltammetry, low and intermediate potential holds in the passive potential domain as well as during open circuit relaxation after anodic polarization in slightly acidified Cl − solution. Ni dissolves at all potentials investigated in this work, Fe and Co are incorporated into oxides or hydroxides in low concentrations whilst Cr and Mn are enriched at passive potentials. At low passivating potentials, Mn(II) dissolves and is incorporated in minor amounts in oxides containing large concentrations of Cr(III). Considerable enrichment in Mn(II)-species occurs relative to Cr(III) in the oxide at 0.1 V vs SCE. Electrochemical impedance spectroscopy suggests the presence of layered oxides with marginal passivation at high Mn(II) levels. The formation of these oxides depends on a combination of thermodynamic and kinetic factors as well as the sequence of passivation.